Women Leaders and Gender Stereotyping in the UK Press A Poststructuralist Approach - Baxter, Judith (Postdisciplinary Studies in Discourse, 2018)
This book explores how the UK press constructs and represents women leaders drawn from three professional spheres: politics, business, and the mass media. Despite significant career progress made by women leaders in these professions, many British newspapers continue to portray these women in stereotyped and essentialist ways: the extent to which this occurs tending to correspond with the political affiliation and target readership of the newspaper. The author analyses news media articles through three fresh perspectives: first, Kanter's women leader stereotypes, second, a feminist agenda spectrum and third, a new 'reflexive' approach based on Feminist Poststructuralist Discourse Analysis. This book will appeal strongly to students and scholars of discourse analysis and media studies, and anyone with an interest in language, gender, leadership and feminism. .